Syādvāda and Artificial Intelligence: Exploring the Linkages - Kushwaha, Ravindra Kumar (International Journal of Religion Education and Law, 2026)
This paper delves into the potential synergies between Syādvāda, a core principle of Jain philosophy, and the ethical development of Artificial Intelligence (AI). Syādvāda, rooted in the concept of Anekāntavāda, asserts that reality is complex and that any statement or decision is only conditionally true, depending on the context and perspective. This philosophy offers a valuable framework for addressing some of the most pressing ethical challenges in AI, such as bias, transparency, and inclusivity. By incorporating the principles of Syādvāda, AI systems can be designed to recognize the multifaceted nature of truth, thereby allowing for more nuanced and balanced decision-making processes. The application of Syādvāda in AI development encourages the consideration of multiple perspectives, which can help mitigate biases inherent in data and algorithms. This approach also enhances the transparency of AI systems by promoting explainability and the presentation of various possible outcomes or decisions, each grounded in different perspectives. Furthermore, Syādvāda supports the creation of more inclusive AI technologies that are sensitive to the diverse cultural, social, and ethical contexts in which they operate. By fostering a more context-aware and ethically robust approach to AI, Syādvāda provides a philosophical foundation that aligns technological advancement with the broader goal of human well-being. The integration of Syādvāda’s principles into AI development can lead to systems that are not only more effective but also more equitable, trustworthy, and adaptable to the complexities of the modern world. As AI continues to evolve and become increasingly integrated into all aspects of life, the insights of Syādvāda offer a path toward more responsible and ethically sound AI technologies.